2017
DOI: 10.1242/dmm.030502
|View full text |Cite|
|
Sign up to set email alerts
|

Early cerebellar deficits in mitochondrial biogenesis and respiratory chain complexes in the KIKO mouse model of Friedreich ataxia

Abstract: Friedreich ataxia (FRDA), the most common recessive inherited ataxia, results from deficiency of frataxin, a small mitochondrial protein crucial for iron-sulphur cluster formation and ATP production. Frataxin deficiency is associated with mitochondrial dysfunction in FRDA patients and animal models; however, early mitochondrial pathology in FRDA cerebellum remains elusive. Using frataxin knock-in/knockout (KIKO) mice and KIKO mice carrying the mitoDendra transgene, we show early cerebellar deficits in mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 86 publications
12
59
0
Order By: Relevance
“…PGC‐1a, the master regulator of mitochondria biogenesis, also plays a role in FRDA development. Lin et al demonstrated that in diseased FRDA mouse models, both PGC‐1a and its downstream effectors are significantly reduced compared to healthy controls. This impairment occurred early in the mitochondrial biogenesis pathway and is considered a potential therapeutic target for FRDA treatment.…”
Section: Mitochondrial Abnormalities Lead To Neurodegenerative Diseasesmentioning
confidence: 99%
“…PGC‐1a, the master regulator of mitochondria biogenesis, also plays a role in FRDA development. Lin et al demonstrated that in diseased FRDA mouse models, both PGC‐1a and its downstream effectors are significantly reduced compared to healthy controls. This impairment occurred early in the mitochondrial biogenesis pathway and is considered a potential therapeutic target for FRDA treatment.…”
Section: Mitochondrial Abnormalities Lead To Neurodegenerative Diseasesmentioning
confidence: 99%
“…According to this hypothesis, "young" and immature iPSC-derived neurons could provide information on early disease mechanisms. Our FRDA CNS neurons do not show any phenotypical deficit like the ones described for other FRDA cell types or animal models (27,50,51,53,(69)(70)(71)(72)(73)(74)(75)(76)(77)(78). Complex I, Complex III and aconitase activity were all similar to unaffected neurons and so were oxygen consumption, spare respiratory capacity, ATP production, reactive oxygen species formation and mitochondrial membrane potential (MMP, data not shown), while others have shown reduction in MMP (79), increased oxidative stress and decreased levels of Fe-S cluster-and lipoic acid-containing proteins (80) in iPSC-derived FRDA neurons compared to controls.…”
Section: Discussionmentioning
confidence: 50%
“…These changes are small but involve multiple aspects of cell metabolism. FRDA neurons show a decrease in mitochondrial protein transcript levels, such as components of the ATP synthase complex and of complex I (black module), all of which have been described in FRDA (23,27,(49)(50)(51). We observe consistent changes in ECM organization, focal adhesion and related signaling (brown and magenta modules and SNs), possibly linked to cytoskeletal abnormalities that have been reported in FRDA cells (52)(53)(54).…”
Section: A Gene Expression Signature Of Frdamentioning
confidence: 93%
“…These PDE inhibitors provide mitochondrial bioenergetics promotion, antioxidant effects, and neuroprotective and neuroregenerative actions. Because decreased mitochondrial biogenesis has been demonstrated in mononuclear cells from peripheral blood of FRDA patients, in FRDA cells and mouse models [64,65], as well as decreased mitochondrial potential membrane and increased ROS production in cerebellar neurons from YG8R mice [46] among other neuronal models [14,27], it would seem that PDE inhibitors may display potential therapeutic benefits in FRDA. Resveratrol, a nonselective PDE inhibitor, increases FXN expression in cellular and mouse models of FRDA and has clinical benefits in FRDA patients by improving oxidative stress and clinical outcomes [50].…”
Section: Discussionmentioning
confidence: 99%